Immobilized Lipase in Resolution of Ketoprofen Enantiomers: Examination of Biocatalysts Properties and Process Characterization - Oliwia Degórska; Daria Szada; Agata Zdarta; Wojciech Smułek; Teofil Jesionowski; Jakub Zdarta (MDPI AG, 2022)
In this study, lipase from Aspergillus niger immobilized by physical immobilization by the adsorption interactions and partially interfacial activation and mixed physical immobilization via interfacial activation and ion exchange was used in the kinetic resolution of the ketoprofen racemic mixture. The FTIR spectra of samples after immobilization of enzyme-characteristic signals can be seen, and an increase in particle size diameters upon immobilization is observed, indicating efficient immobilization. The immobilization yield was on the level of 93% and 86% for immobilization unmodified and modified support, respectively, whereas activity recovery reached around 90% for both systems. The highest activity of immobilized biocatalysts was observed at pH 7 and temperature 40 °C and pH 8 and 20 °C for lipase immobilized by physical immobilization by the adsorption interactions and partially interfacial activation and mixed physical immobilization via interfacial activation and ion exchange, respectively. It was also shown that over a wide range of pH (from 7 to 10) and temperature (from 20 to 60 °C) both immobilized lipases retained over 80% of their relative activity, indicating improvement of enzyme stability. The best solvent during kinetic resolution of enantiomers was found to be phosphate buffer at pH 7, which obtained the highest efficiency of racemic ketoprofen methyl ester resolution at the level of over 51%, followed by enantiomeric excess 99.85% in the presence of biocatalyst obtained by physical immobilization by the adsorption interactions and partially interfacial activation.